2022
DOI: 10.3390/ani12192555
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Drifting Larval Fish Community in a Large Spawning Ground in the Middle Pearl River Using DNA Barcoding

Abstract: Resolving the species composition of a larval pool in a spawning ground can provide novel insights into regional fish stocks and can support the development of effective monitoring and conservation policies. However, it is challenging to identify fish larvae to species due to their high diversity and dramatic phenotypic changes over development. In this study, we collected fish larvae in the Dongta spawning ground (Guiping City, Guangxi Province, China) in the middle reaches of the Pearl River between May and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…There are many examples suggesting that the decline or obstruction of their migration routes caused by dams, culverts, or other anthropogenic activities, can impact freshwater biodiversity by directly decreasing the migratory fish populations (Antonio et al, 2007; Bao et al, 2019; Benitez et al, 2022; Frissell, 1993; Hatry et al, 2016; Pasha et al, 2015; Silva et al, 2018; Tan et al, 2022). For example, Chen et al (2022) found various economic migratory species (e.g., Ctenopharyngodon idella , Hypophthalmichthys nobilis , and Mylopharyngodon piceus ) which were historically common in the Pearl River have been rarely identified in the recent survey due to the long‐term obstruction of the Changzhou Dam. Consequently, dam removal (Silva et al, 2018; Whittum et al, 2023) and installation of fish passage facilities (i.e., fishways) (Clay, 1995; Ovidio et al, 2020) have been increasingly considered in an attempt to restore river connectivity worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…There are many examples suggesting that the decline or obstruction of their migration routes caused by dams, culverts, or other anthropogenic activities, can impact freshwater biodiversity by directly decreasing the migratory fish populations (Antonio et al, 2007; Bao et al, 2019; Benitez et al, 2022; Frissell, 1993; Hatry et al, 2016; Pasha et al, 2015; Silva et al, 2018; Tan et al, 2022). For example, Chen et al (2022) found various economic migratory species (e.g., Ctenopharyngodon idella , Hypophthalmichthys nobilis , and Mylopharyngodon piceus ) which were historically common in the Pearl River have been rarely identified in the recent survey due to the long‐term obstruction of the Changzhou Dam. Consequently, dam removal (Silva et al, 2018; Whittum et al, 2023) and installation of fish passage facilities (i.e., fishways) (Clay, 1995; Ovidio et al, 2020) have been increasingly considered in an attempt to restore river connectivity worldwide.…”
Section: Introductionmentioning
confidence: 99%